2010
DOI: 10.1186/1756-9966-29-109
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for vimentin: the potential biomarker for predicting melanoma hematogenous metastasis

Abstract: BackgroundThe incidence of malignant melanoma (MM) was occurring at a faster rate than for most neoplasm worldwide, and melanoma metastasis is still the most formidable problem. So it is necessarily to find some biomarkers associated with melanoma metastasis.MethodsIn our study, 8 spontaneous lung metastatic mice models were created by B16F10 subcutaneously transplantation. The differential protein profiles of two kinds of subcutaneous transplanted tumor tissues, which was parental B16F10 (B16 group) and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 30 publications
0
56
0
Order By: Relevance
“…Thus, Panx1 knockdown was not only causing a re-differentiation of the melanoma phenotype into a more melanocytic one, but it appeared to have changed the tumorigenic and metastatic properties of these cells. Vimentin has been identified as a useful biomarker for melanoma metastasis, as its overexpression is observed in patients with primary melanoma with hematogenous metastasis but not associated with metastasis to the lymph nodes (38). Vimentin has also been reported to regulate Hsc70, which is one of the heat shock cognate proteins that was also down-regulated in Panx1-reduced cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Panx1 knockdown was not only causing a re-differentiation of the melanoma phenotype into a more melanocytic one, but it appeared to have changed the tumorigenic and metastatic properties of these cells. Vimentin has been identified as a useful biomarker for melanoma metastasis, as its overexpression is observed in patients with primary melanoma with hematogenous metastasis but not associated with metastasis to the lymph nodes (38). Vimentin has also been reported to regulate Hsc70, which is one of the heat shock cognate proteins that was also down-regulated in Panx1-reduced cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Interestingly, the high expression of PGK-1 is significantly correlated with tumor progression, metastasis and multidrug resistance in various cancers. 21,22,[24][25][26] It has also been reported that the expression of PGK-1 in PCa cells could induce bone formation 27 and that cancer-associated fibroblasts, which showed strong expression of PGK-1, could promote PCa growth, 28 suggesting that PGK-1 plays important roles in PCa development, progression and bone metastasis. In addition, both PGK-1 and AR genes are located within Xqll-Xql3 region and PGK-1 short tandem repeat polymorphism linkage to AR in the expression of miR-29a has been found to be correlated with short survival, more invasive phenotype, and early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vimentin showed overexpression in pancreatic cancers and increased the invasive potential of pancreatic cancer cells [39] [40]. In addition, vimentin expression was shown to be elevated in aggressive breast cancer [41] primary malignant melanomas [42], CNS tumors [43]. Its overexpression in all these types of cancer was very well correlated with increased migration and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 81%